PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN MAHASISWA DAN CITRA PERGURUAN TINGGI PADA AKADEMI KEBIDANAN SALMA SIAK - Imran, Imran; Indrayani, Siska (Ensiklopedia of Journal, 2020)
This research aims to analyze the effect of quality of service to the satisfaction of students, and higher education images on the Salma’s midwifery academy students at Siak regency. The number of research samples are all students, 85 by census method. Then, datas collecting through questionnaires direct spreading by using a Likert scale. Analytical datas method in this research using two stages regression through reliable statistical measured by SPSS version 20 software. Research result shows that independent variables, quality of service which consist of tangibles, realibility, Responsiveness, Assurance, Empathy, and technical having significant influence and positive towards student’s satisfaction, then, student’s satisfaction having significant influence and positive towards higher education images, this research result is expected to intensify student preference to study at Salma’s midwifery academy.